ASI thresher for reducing postharvest loss in rice production in Senegal - CGIAR Research Program on Rice (2021)
ASI is already diffuse at large scale. It is produced and marketed by private and local fabricators. It is available in Senegal, Cameroon, Chad, Côte d’Ivoire, Ghana, Mali, Mauritania, Burkina Faso, Sierra Leone, Ethiopia, The Gambia and Nigeria